Influence of a new combination anthelmintic aversect plus on dog’s organism - K. G. Kurochkina; Z. G. Musaev (Российский паразитологический журнал)
It’s determinate that a new combination anthelmintic aversect plus at dose levels 0,5 mg/kg and 5 mg/kg of body weight according to aversect-3 and praziquantel, don’t show negative effects on blood and no specific resistance of dogs.